2001
DOI: 10.1002/ppul.1157
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic equivalence of three metered‐dose inhalers containing salbutamol (Albuterol) in protecting against methacholine‐induced bronchoconstriction in children with asthma

Abstract: Many pharmaceutical companies sell salbutamol in metered-dose inhalers (MDI) for the treatment of asthma. However, the therapeutic equivalence of the more recently released generic products has not been compared with the original patented product in children. Twenty children with mild to moderate asthma, presently asymptomatic and with normal lung function, were randomly allocated to receive 200 microg of inhaled salbutamol (Albuterol) from three MDIs prepared by different manufacturers: the original Glaxo pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…Consequently, the US Food and Drug Administration advisory committees have recommended the use of methacholine challenge testing for assessing the pharmacodynamic properties of inhaled β 2 agonists [17]. A number of previous studies have used methacholine challenges to compare short‐acting inhaled β 2 agonists [18, 19]. Furthermore, a study using methacholine challenges to compare the long‐acting β 2 agonists formoterol and salmeterol was able to demonstrate a difference in dose–response that was not reflected in FEV 1 changes [12].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the US Food and Drug Administration advisory committees have recommended the use of methacholine challenge testing for assessing the pharmacodynamic properties of inhaled β 2 agonists [17]. A number of previous studies have used methacholine challenges to compare short‐acting inhaled β 2 agonists [18, 19]. Furthermore, a study using methacholine challenges to compare the long‐acting β 2 agonists formoterol and salmeterol was able to demonstrate a difference in dose–response that was not reflected in FEV 1 changes [12].…”
Section: Discussionmentioning
confidence: 99%
“…Any method used in bioequivalence studies should be reproducible and have a dose–response relationship. Although a dose–response relationship has been reported [2] a bronchoprovocation study comprising two doses from an innovator and generic product suggested that therapeutic equivalence may have been shown due to the plateau of the dose–response curve [3]. This assumption was made because the two products had a different emitted fine particle dose determined by in vitro methods.…”
Section: Introductionmentioning
confidence: 99%
“…Although published clinical studies demonstrated that substituting brand name salbutamol with generic salbutamol resulted in an equivalent clinical response, [4][5][6] anecdotal reports of failure due to a lack of efficacy or adverse effects were not uncommon. In a carefully controlled clinical study, the therapeutic equivalence of three salbutamol MDIs was even demonstrated in a paediatric population, 7 but clinicians learning of 'failure' of a generic MDI product from their patients may be more likely to trust the report from their own patients than the results of a scientifically rigorous study conducted by unknown investigators. It is likely that any changes in 'objective measures', such as a decline in FEV 1 , would provide further 'concrete' evidence of the failure of the new generic product.…”
Section: Discussionmentioning
confidence: 99%